Simulation of the corrosion-induced damage on aluminum alloy 2024 specimens with equivalent surface notches (Fracture and Structural Integrity, 2019)
The effect of corrosion environment aggressiveness on the tensile mechanical properties degradation of AA2024-T3 was investigated. Tensile specimens were pre-corroded for various exposure times to different corrosive solutions, i.e., exfoliation corrosion (EXCO) and 3.5 wt. % NaCl. Then they were tested mechanically. In non-corroded specimens, surface notches of various depths were machined to simulate the degradation of the tensile mechanical properties due to the presence of artificial surface defects. A mechanical model was developed to correlate the corrosion-induced tensile ductility degradation due to pitting and possible hydrogen embrittlement with the equivalent artificially induced surface notches. The cases studied for this physical correlation were: a) EXCO exposure with artificial notches, b) EXCO with 3.5 wt.% NaCl exposure and c) 3.5 wt.% NaCl exposure with artificial notches. Higher correlation was noticed for short exposure times for all cases where the dominant degradation mechanism is slight pitting formation. It was found that 1 h EXCO exposure is equivalent to 92 h exposure to NaCl solution regarding the tensile ductility degradation while 24 h EXCO exposure has the same effect on ductility decrease with a 240 μm surface notch or 4000 h exposure to NaCl solution.
Keywords: Corrosion; Notches; Mechanical properties; Aluminum alloy